Correlation Between Proteolytic Enzymes and Microangiogenesis in Degenerative Intervertebral Disc Nucleus - Dong Chen; Xin Jiang (Journal of Investigative Surgery, 2021)
Objective To investigate the correlation between proteolytic enzymes and microangiogenesis in degenerative intervertebral disc nucleus. Methods: Forty patients with degenerative disc nucleus pulposus who were admitted to our hospital were selected incase group and 20 healthy subjects were selected into the normal group. The specimens from the case group and the control group were collected to observe the degeneration of nucleus pulposus tissues with different degrees of classification, including H&E staining and immunohistochemical staining, and observe cathepsin such as aminopeptidase and vascular endothelial positive cells. The distribution of microvessels was also performed by the Weidner method. Results: After H&E staining, chondrocytes in the normal group clustered in the cartilage depression under the microscope. The matrix staining was uniform, while the number of chondrocytes in the case group decreased, and the nucleus was lightly stained or disappeared. Immunohistochemistry assay revealed little or no expression of aminopeptidase N (APN) and leucine aminopeptidase (LAP) in the nucleus pulposus of the normal group, but noticeable APN and LAP expressions in the degenerative intervertebral disc nucleus. Endothelial cells were stained singly or in clusters by CD31-labeled microvascular endothelial growth factor (VEGF). Conclusion: The expression level of various proteolytic enzymes such as aminopeptidase in the intervertebral disc and the linear relationship between microvessel formation and nerve fiber ingrowth in the intervertebral disc are helpful to further explore the molecular level of disc degeneration and pathophysiological mechanisms to aid clinical diagnosis and treatment of such diseases.